Analysis of the producer price of Hungarian raw milk in international comparison - Blaskó, Beáta (Applied Studies in Agribusiness and Commerce, 2012)
Although the dairy market crisis eased in 2011, Hungarian dairy farmers still find it difficult to produce milk profitably. As a result of the crisis, many dairy farmers abandoned milk production or reduced the size of their dairy herds in 2009 and 2010. Today, many of farmers are also considering ceasing production, in spite of the fact that the global dairy industry is facing an upturn. A dairy farm can operate profitablyy in three ways: 1) if it can reach a relatively high level of producer price 2) if it can increase milk production per cow 3) if it can achieve a relatively low cost of production. In the present study, I primarily analyse the development of the Hungarian producer price of raw milk in international comparison. Next, I list those factors which directly or indirectly influence the producer price of raw milk. Finally, I examine the relationship among disposable income, milk consumption and milk price. Since the start of 2009, the dairy market has been confronted with a period of extraordinary law prices. After bottoming out, prices had begun to slowly stabilise during the second half of 2009. By the end of that summer, international prices had started to strengthen and the last quarter of 2009 was characterized by a steady rise in prices. The strong recovery in prices experienced after 2009 was triggered by increased demand, mainly from oil exporting countries, but also from China. The price increase, however, reflected a significant increase in input costs in Hungary; the high level of feed prices and the unfavourable change in the macroeconomic environment must be stressed. The rising excise duty on diesel fuel and the VAT increase had a direct impact on Hungarian dairy farmers. These negative factors have increased the costs of the sector, narrowing the ability of those active in it to operate efficiently.